VOLUME AND BIOMASS PARAMETERS IN ONE HECTARE OF SAVANNAH IN PLANALTINA, GOIÁS, BRAZIL - Imaña-Encinas, José (2025)
The tree vegetation was studied over a representative hectare of the savanna in the sensu stricto, located in Planaltina, State of Goiás (Brazil). In the study area, 490 trees with a diameter at breast height (DBH) of 5 cm or greater were measured. The average diameter, stand density (in number of trees per hectare and in basal area), the volume of green wood with bark, and the dry weight of the wood were measured for the entire forest stand as well as for each of the 51 tree species present. The stand density was found to be lower than that of analogous forest formations, with a notable presence of smaller diameter classes (DBH less than 13 cm), suggesting that the protected area studied had been subject to past logging activities. The obtained timber stocks were 16 m³/ha, corresponding to 11,927 kg/ha of dry woody biomass. Sixty-seven percent of the stock (by volume and weight) consisted of trunks, with the remainder being branches. The majority of the trunk volume (56%) and biomass (61%) came from seven species: Hymenaea stigonocarpa, Qualea parviflora, Guapira nixia, Caryocar brasiliense, Sclerolobium paniculatum, Pouteria ramiflora, and Pterodon polygalaeflorus.